Online Mental Health Assessments of COVID-19 Patients in South Korea - Lee, Jung Hyun; Lee, Dayoung; Hyun, Soyoen; Hong, Ji Sun; Kim, Chang-Hoon; Kim, Woojin; Sim, Minyoung (Frontiers in Psychiatry, 2021)
Experiences of infectious diseases cause stressful and traumatic life events, hence, COVID-19 patients could suffer from various mental health problems requiring psychological support services. This study investigates the severity of mental health problems among confirmed COVID-19 patients. From March to November 2020, we collected the data from 118 COVID-19 patients who voluntarily participated in the National Center for Disaster Trauma’s online mental health assessment consisting of self-report scales like Primary Care of Posttraumatic Stress Disorder screen (PC-PTSD), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Patient Health Questionnaire-15 (PHQ-15), and P4 Suicidality Screener. For control, 116 other disaster-experienced and 386 non-COVID-19-experienced participants were recruited. The COVID-19 patients showed more severe symptoms including post-traumatic symptoms, depression, anxiety, and somatic symptoms than control groups across all four screening scales (p<.001). Regarding high-risk, COVID-19 patients had an increased association with high-risk compared to the comparison groups (PC-PTSD: OR = 24.16, 95% CI = 13.52-43.16 p<.001; PHQ-9: OR = 14.45, 95% CI = 8.29-25.19, p<.001; GAD-7: OR = 20.71, 95% CI = 10.74-39.96, p<.001 PHQ-15: OR = 5.65 95% CI = 3.44-9.25, p<.001; P4: OR = 14.67, 95% CI = 8.95-25.07, p<.001). This study implies that there is a high-risk of overall mental health problems, especially stronger associations of post-traumatic stress symptoms, in COVID-19 patients. These findings should inform practitioners about the psychological responses to COVID-19 experiences and help to prepare appropriate interventions and services for the incremental number of confirmed cases.